Strategi Pemasaran dalam Meningkatkan Daya Saing Destinasi Pariwisata Super Prioritas Labuan Bajo (Jurnal Ekonomi Bisnis dan Akuntansi, 2026)
Labuan Bajo has been designated as one of Indonesia’s Super Priority Tourism Destinations, possessing strong competitive advantages derived from its unique natural attractions, particularly Komodo National Park, marine tourism, and distinctive island landscapes. This study aims to analyze marketing strategies in enhancing the competitiveness of Labuan Bajo as a super priority destination amid increasing competition and sustainability challenges. Using a qualitative approach, data were collected through in-depth interviews, observations, and documentation involving key stakeholders, government representatives, local communities, and domestic and international tourists. The findings indicate that marketing strategies play a crucial role in strengthening destination competitiveness, with digital marketing through social media, official websites, and online travel platforms proving effective in building destination image and attracting visitors. However, marketing efforts remain concentrated on iconic attractions and are not yet fully supported by equitable infrastructure development, consistent service quality, and inclusive tourist information, particularly for international visitors. Therefore, an integrated and adaptive marketing strategy supported by service improvement, infrastructure strengthening, destination diversification, and sustainable management is essential to ensure long-term competitiveness and sustainable tourism growth in Labuan Bajo.